The Halal Capsule Shell in the Perspective of Comparative Islamic Law and Health Law: Opportunities and Challenges - Rafianti, Fitri; Risdawati, Irsyam; Andafi, Muhammad (Faculty of Law, Universitas Pekalongan, 2024)
This research aims to analyze and compare the perspectives of Islamic law and health law regarding the use of halal capsule shells. This study is a comparative research that explores legal, ethical, and health aspects in the use of capsule shells that meet halal criteria. Using a qualitative approach, this research collected data from various relevant sources, including Islamic legal texts, health regulations, and related scientific literature. The results show that there are both similarities and significant differences in the standards and interpretations of halal between Islamic law and health law. From the perspective of Islamic law, the halal status of capsule shells is determined by the source of materials and the manufacturing process, while health law focuses more on the safety and effectiveness of the product. The study also identifies opportunities, such as a large market potential for halal products, and challenges, including the need for standardized and integrated halal certification. This research provides new insights into the importance of harmonizing the principles of halal in Islam with health standards, which are crucial not only for Muslim producers and consumers but also for broader social and economic integration. Recommendations for further research and related policies are presented to support the sustainable development of the halal capsule industry.